Impact of paved front gardens on current and future urban flooding. (12th February 2016) - Kelly, D.A.
Abstract: Domestic front gardens provide a valuable asset in the control of surface water runoff in towns and cities. Projected increases in future rainfall make this asset increasingly important, while growing trends of paving over front gardens puts this asset at jeopardy. The contribution of paved front gardens to the overall urban flood burden is often neglected. This paper quantifies rainwater runoff from a typical front garden using numerical simulation. Runoff is quantified in terms of both current and future rainfall intensities and in relation to variables of impermeable cover and soil type. Garden runoff is shown to be directly proportional to the area of impermeable cover and rainfall intensity. Soil type is important in determining runoff with faster infiltrating soils experiencing higher percentage increases in runoff if paved over, and slower infiltrating soils experiencing increased runoff volumes even from unpaved gardens in response to increased rainfall due to future climate change.